The Effect of Non-Compliance with Medication on Multidrug Resistant of Tuberculosis - Widya Kurnianingsih; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2020)
Background: Multidrug Resistant Tubercu